1987
DOI: 10.1093/bja/59.5.596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stretch Exercises on Suxamethonium Induced Fasciculations and Myalgia

Abstract: Muscle fasciculations and pain following the administration of suxamethonium were assessed in a group of patients who performed a series of stretch exercises approximately 1 h before operation. Comparison was made with a group who received suxamethonium but no pretreatment. Fasciculations were significantly reduced in the exercised group, and the incidence of muscle pain decreased from 52% in the untreated group to 12% in the exercised group. A significant relationship was shown between the severity of visible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…If it is assumed that postoperative myalgia is caused by damage to muscles after fasciculations, stretching exercises may reduce postoperative myalgia. Stretching exercises have been shown to reduce significantly the incidence of both fasciculations and postoperative muscle pains [40]. The muscle stretch receptors are progressively desensitised as the receptor potential adapts under conditions of prolonged slow stretch.…”
Section: Methods Used To Reduce Myalgiamentioning
confidence: 99%
See 1 more Smart Citation
“…If it is assumed that postoperative myalgia is caused by damage to muscles after fasciculations, stretching exercises may reduce postoperative myalgia. Stretching exercises have been shown to reduce significantly the incidence of both fasciculations and postoperative muscle pains [40]. The muscle stretch receptors are progressively desensitised as the receptor potential adapts under conditions of prolonged slow stretch.…”
Section: Methods Used To Reduce Myalgiamentioning
confidence: 99%
“…With a reduction in the rate of gamma efferent discharge from the muscle spindles, the excitability of alpha motor neurones is modified. It has been suggested that this may increase the threshold for motor units, thus altering the action of succinylcholine [40, 41]. It is unfortunate that no further studies are available to substantiate the results of the original work, since stretching exercises cost nothing and are safe.…”
Section: Methods Used To Reduce Myalgiamentioning
confidence: 99%
“…pancuronium, vecuronium, pipecuronium and rocuronium) are generally free of the troublesome side effects associated with non‐steroidal neuromuscular relaxants (e.g. histamine release (Basta et al , 1983) and malignant hyperthermia (Magee et al , 1987)).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-treatment with a small dose of a non-depolarizing neuromuscular blocking agent prior to the administration of succinylcholine, remains the most commonly employed method, dating back to a 1957 report of the use of gallamine [7]. Other methods including stretching exercises and supplementation of vitamin C, have been reported to be effective [22,23]. Since it has been postulated that calcium influx enhances the intensity of muscle fiber contractions, inducing spindle damage and subsequent pain, pre-treatment with medications such as dantrolene which interfere with intracellular calcium release have been reported to be effective [24].…”
Section: Discussionmentioning
confidence: 99%